Taxonomic revision of the spider genera Agyneta and Tennesseellum (Araneae, Linyphiidae) of North America north of Mexico with a study of the embolic division within Micronetinae sensu Saaristo & Tanasevitch 1996 - Dupérré, Nadine (Zootaxa, 2013)
The genera Agyneta Hull 1911 and Tennesseellum Petrunkevitch 1925 are revised for North America north of Mexico. The synonymy of Meioneta Hull 1920 with Agyneta Hull 1911 proposed by Saaristo 1973 is corroborated. The North American fauna north of Mexico of Agyneta now includes a total of 69 species, of which 31 are new species: A. watertoni n. sp., A. perspicua n. sp., A. aquila n. sp., A. yukona n. sp., A. darrelli n. sp., A. bucklei n. sp., A. erinacea n. sp., A. craw-fordi n. sp., A. vinki n. sp., A. panthera n. sp., A. miniata n. sp., A. danielbelangeri n. sp., A. pistrix n. sp., A. flax n. sp., A. barfoot n. sp., A. sandia n. sp., A. spicula n. sp., A. grandcanyon n. sp., A. chiricahua n. sp., A. crista n. sp., A. tuberculata n. sp., A. catalina n. sp., A. ledfordi n. sp., A. platnicki n. sp., A. bronx n. sp., A. paquini n. sp., A. girardi n. sp., A. flibus-crocus n. sp., A. delphina n. sp., A. okefenokee n. sp. and A. issaqueena n. sp. The genus Tennesseellum includes two spe-cies, with one new species, T. gollum n. sp. Ten new synonyms are recognized: Meioneta grayi Barnes 1953 = Anibontes mimus Chamberlin 1924; Meioneta dactylata Chamberlin & Ivie 1944, Meioneta officiosa (Barrows 1940) = Meioneta micaria (Emerton 1882); Meioneta imitata Chamberlin & Ivie 1944 = Meioneta leucophora Chamberlin & Ivie 1944; Meioneta ferosa (Chamberlin & Ivie 1943) = Meioneta fillmorana (Chamberlin 1919); Meioneta fuscipes Chamberlin & Ivie 1944 = Meioneta floridana (Banks 1896); Meioneta alaskensis Holm 1960 = Meioneta maritima (Emerton 1919); Meioneta meridionalis (Crosby & Bishop 1936), Meioneta zebrina Chamberlin & Ivie, 1944 = Meioneta parva (Banks 1896); Meioneta zygia (Keyserling 1886) = Meioneta fabra (Keyserling 1886). Ten informal species groups are proposed based on the study on the male palpal conformation of the embolus and radical division; these groups are not intened to be phylogenetic hypotheses. The limits and composition of the subfamily Micronetinae sensu Saaristo & Tanasevitch 1996 are discussed.